Anti-corruption preachers: Training for cultural da'wah at the Paguyuban Mubalig Prenggan, Yogyakarta - Suyadi, Suyadi; Waharjani, Waharjani; Sumaryati, Sumaryati; Sukmayadi, Trisna (Universitas Muhammadiyah Magelang, 2021)
Paguyuban Mubalig Prenggan is an association of anti-corruption preachers under the coordination of the Muhammadiyah Branch Leaders who have cultural assets of karawitan art. Lately, the role of the anti-corruption preacher is very much needed as corruption in Covid-19 funds is increasingly rampant. Ironically, since the Covid-19 pandemic, the anti-corruption cultural da'wah activities of the Paguyuban Mubalig Prenggan have stopped completely. This is due to the lack of mastery of digital technology for virtual da'wah. The purpose of this community service program is to improve virtual cultural da'wah skills as an effort to prevent corruption during the Covid-19 pandemic. The implementation of the activity uses the Participatory Action Research (PAR) method with three stages, namely analysis of the current situation, collaboration of anti-corruption song creations, and virtual anti-corruption cultural propaganda training and assistance. This community service increases the empowerment of partners in three aspects. First, re-activating cultural da'wah which had been completely stopped. Second, the creation of